The JVC Video anthology of world music and dance - Ichikawa, Katsumori; Nakagawa, Kunihiko; Victor Company of Japan (Firm) (Japan : Victor Company of Japan, 1990)
Presents examples of the diversity of musical and dance forms practiced today throughout the world
vol. 6. Southeast Asia I: Vietnam/Cambodia.-- vol. 7. Southeast Asia II: Thailand/Burma.-- vol. 8. Southeast Asia III: Malaysia/Philippines.-- vol. 9. Southeast Asia IV: Indonesia 1.-- vol. 10. Southeast Asia V: Indonesia 2
Title from container
Keywords: Folk music; Folk dancing; Folk dance music